Determinant Factors Analysis of Turnover Intention in Y Generation at Bank Syariah Indonesia, Semarang City - Mila Sartika; Farida Akhmad (Velocity: Journal of Sharia Finance and Banking, 2023)
The banking business must be able to adjust to the ongoing technological advances by leveraging these advancements to keep up with innovation. A new generation is currently joining the workforce. Leaders of businesses should get ready to welcome the Y Generation into their sector or organization because it may present both an opportunity and a challenge for Indonesia’s future. Companies need to pay more attention to employee turnover rates because the Y Generation is associated with a relatively high desire to leave the workforce. An in-depth analysis of the impact of job engagement, work-life balance, and Y Generation rewards on turnover intention is the goal of this study. The researcher employed primary data in the form of a questionnaire to investigate this problem. Software SPSS version 26 was used for data analysis. Managers can utilize this information to address issues with employee turnover intention. The study’s findings show that the work engagement variable significantly reduces the likelihood of turnover. The work-life balance variable then significantly reduces the likelihood of turnover. The incentive variable also significantly influences turnover intention in the wrong direction.